BIOEFFICACY OF ALLIUM SATIVUM EXTRACT IN THE CONTROL OF TRICHODINA AND EPISTYLIS SPP OF CLARIAS GARIEPINUS IN GWAGWALADA TOWN FCT, ABUJA - U.N., GIMBA (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2015)
Parasitological examination was carried out in one hundred and forty-five naturally collectedClarias gariepinus from Usuma River in Gwagwalada. It revealed skin and gill infestation withectoparasitic protozoan Trichodina and Epistylis and monogenean Tetrahymena spp. withaverage 20, 15 and 25%, respectively. The average total ectoparasitic infestation in theexamined catfish was 60%.The significance of herbal control measures using A. sativum as anew method to eradicate such parasites, was evaluated. A bioassay of 96 hours LC50 of A.sativum emphasized that its value was 192mg/L. The herbal control with A. sativum was safe andeffective to treat the ectoparasitic protozoa Trichodina and Epistylis spp. at dose 20mg/L, but notsuitable for treating the monogenean Tetrahymena spp.